A distributed camera library design for telepresence - Ohl, Stephan; Willert, Malte; Staadt, Oliver (Workshop on Software Engineering and Architectures for Realtime Interactive Systems (Print), 2013)
We present a distributed dataflow-based camera library design. It is tailored to the special needs of distributed acquisition and rendering telepresence systems with inhomogeneous camera arrays. We discuss a variety of design decisions: choice of dataflow concept, memory management, camera interface abstraction and important built-in functionality.